ANALISIS POSISI PENDIDIKAN ISLAM DALAM SISTEM PENDIDIKAN DI INDONESIA - Iqbal, Moch. (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2023)
AbstractIslamic education is education that teaches good values which are then implemented in life. Islamic education is a process of forming human beings in the direction they aspire to, including Indonesia, which has a majority population of adherents of the Islamic religion. Islamic education itself has an important role in the history of the development of the Indonesian nation, especially in terms of the historical dimension where Islamic education has been a formal education for centuries known as pesantren. The aim of this research is to find out the position of Islamic education in the national education system because in order to make a balanced human being from an intellectual point of view, religious education is needed, namely Islamic education in order to achieve national education goals. The method used in this study uses a qualitative research method with a type of library research (library research). Based on the results of the study it can be concluded that Islamic education in the national education system is that Islamic education occupies a position as a formal, non-formal, informal, and religious institution. The position of Islamic Education in the National Education System is as an educational institution, subjects, and islamic values. Islamic education is a sub-ordinate within the National Education System, meaning that Islamic Education is part of the National Education System which cannot stand alone. Keywords: Education, Islamic Education, National Education